Pleomorphic adenoma of the palate - A case series - S Parvathi; G S Asokan; Narmatha Namachivayam (SRM Journal of Research in Dental Sciences, 2023)
Rationale and Patient Concerns: This article highlights the case report of pleomorphic adenoma (PA) of the palate in a 37-year-old female patient and a 34-year-old male patient. Diagnosis and Investigations: Fine-needle aspiration cytology and computed tomography scan were performed to arrive at diagnosis. Interventions: Surgical excision was the most effective treatment plan. These tumors are mostly painless and are more common in the parotid gland, followed by the palate in case of minor salivary gland involvement. The tongue, tonsil, pharynx, floor of the mouth, lip, buccal mucosa, and retromolar region are other intraoral locations for this tumor. Lessons: PA is the most common benign salivary gland tumor, accounting for about 40%–70% of all major and minor salivary gland tumors. Palatal swellings are the most common complaints of patients; however, PA of the palate is a rare diagnosis. PA, also known as a benign mixed tumor, generally occurs in the parotid salivary gland and rarely in the minor salivary gland.